Otimização do processo de hidrólise da mandioca in natura, com o uso de enzimas amilolíticas e pectinolítica - Collares, Renata Monteiro (2011)
Cassava is an important source of nutrients, and also of great importance as agro-industrial raw materials and can be used to produce ethanol. Through the process of hydrolysis, acid or enzyme, starch is converted into sugars. The hydrolyzed by enzymes are the most important commercial modified starches such as dextrins, maltose, etc. This paper aims at the use of cassava "in natura" disposal, to determine the optimal conditions for hydrolysis step, through the use of pectinolytic and amylolytic enzymes. We developed a Central Composite Rotational Design, 24, with four repetitions of the center point and eight trials with the axial points, which were used as independent variables pectinase dosage (0; 2,35; 4,7; 7,05 and 9,4 μL/g mat.seca) dose of amyloglucosidase (0,36; 0,52; 0,68; 0,84 and 1μL/g starch), diluting the cassava/water (1:1; 1:1,41; 1:2; 1:2,59 and 1:3) and hydrolysis time (4, 21, 38, 55 and 72 hours after the addition of the last enzyme) being kept constant dose of α-amylase (0.8mL/g starch) for all tests. The dependent variables analyzed were °Brix and efficiency of hydrolysis. The Brix is directly related to the amount of soluble solids, and therefore the greatest value found was 19°Brix, who used the test dilution cassava/water 1:1, independent of changes in other factors. The optimum process conditions was found using the following parameters: Dosage of amyloglucosidase of 0,84mL/g starch; pectinase dosage of 7,05mL/g mat.seca; Dilution of cassava solution/water 1:1,41, and hydrolysis time (after the last addition of enzyme) for 21 hours, with an efficiency of 100% hydrolysis. The presence of pectinase did there was a 20% increase in the efficiency of hydrolysis, compared with trials that have not used it.